2012
DOI: 10.1080/02508060.2012.688189
|View full text |Cite
|
Sign up to set email alerts
|

Optimization and simulation modelling for operation of the Zayandeh Rud Reservoir

Abstract: This paper combines optimization (LINGO) and simulation (HEC-ResSim) models to determine monthly operating rules for the Zayandeh Rud Reservoir system in Iran. Based on the optimized flow determined in the single-objective framework, system behaviour was simulated over 47 years. The results show that optimizing the operation of Zayandeh Rud Reservoir could increase its storage by 88.9% and increase the reliability index of regulated water for all downstream demands by over 10%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Many researchers, such as Bozorg Haddad et al (2008) and Montazar et al (2010), applied LINGO to evolve an optimal allocation plan of surface and ground water for various hydrosystem types. In another study, Ziaei et al (2012) combined LINGO and the Hydrologie Engineering Center's Reservoir System Simulation (HECResSim) models to determine monthly operating rules for the Zayandeh-Rud Reservoir system in the central part of Iran. In their study, system behavior was simulated over 47 years and the results showed that optimizing the operation of Zayandeh-Rud Reservoir could increase its storage by 88.9%, and increase the reliability index of regulated water for all downstream demands by over 10%.…”
Section: Linear Programming and Lingomentioning
confidence: 99%
“…Many researchers, such as Bozorg Haddad et al (2008) and Montazar et al (2010), applied LINGO to evolve an optimal allocation plan of surface and ground water for various hydrosystem types. In another study, Ziaei et al (2012) combined LINGO and the Hydrologie Engineering Center's Reservoir System Simulation (HECResSim) models to determine monthly operating rules for the Zayandeh-Rud Reservoir system in the central part of Iran. In their study, system behavior was simulated over 47 years and the results showed that optimizing the operation of Zayandeh-Rud Reservoir could increase its storage by 88.9%, and increase the reliability index of regulated water for all downstream demands by over 10%.…”
Section: Linear Programming and Lingomentioning
confidence: 99%
“…(b) During the operational period, reservoir storage (S i,j ) must be higher than dead storage (S min ) and lower than active storage (S max ) S i,j ≤ S max S i,j ≥ S min (3) where S i,j is the reservoir storage during operation time, S max is active storage, and S min is dead storage. (d) Meeting minimum sector demand priorities: As the reservoir cannot meet all demands over the operation period, the following constraint for minimum allowable releases was implemented (as proposed by Ziaei et al [1],Goodarzi et al [4]):…”
Section: Optimisation Toolmentioning
confidence: 99%
“…Available freshwater resources in rapidly developing countries are becoming scarce due to higher demands from industrial, recreational, municipal, and agricultural sectors [1,2]. In addition, socioeconomic developments can lead to significant changes in land-use, which can subsequently impact on water resources critical for downstream economic development [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation